Desenvolvimento de sensores eletroquímicos baseados em nanotubos de carbono e polímeros de ácido ferúlico e capsaicina para detecção e quantificação de 3-nitro-L-tirosina, epinefrina e dopamina - Silva, Leonardo Vieira da (2017)
This thesis reports the development of different electrochemical sensors based on carbon nanotubes (CNT) for the detection and determination of analytes of biological relevance, with evaluation of the analytical and kinetic parameters. The work is divided into three parts. In the first part, the electrochemical study of 3-nitro-L-tyrosine (3-NT) in protic medium is described, using the techniques of cyclic voltammetry and differential pulse. The development of a sensor based on CNT for the determination and quantification of 3-NT, is also shown, with a linear range of 10 - 100 μmol L-1 and a detection limit of 0.42 μmol L-1 in the cathodic range. In the anodic range, a linear range of 10 - 60 μmol L-1 and a detection limit of 1.83 μmol L-1 were obtained. In the second part, a sensor was developed based on CNT with electrochemically generated ferulic acid (FA) polymer, generated in situ to determine dopamine (DA). The techniques used to perform this work were cyclic voltammetry and chronoamperometry, which were used to evaluate kinetic and analytical parameters. Through chronoamperometry and the use of the Cottrell equation, the diffusion coefficient (DDA) and catalytic constant (kcat) values determined for DA were 2.48 x 10-6 cm2 s -1 and 1.15 X 104 M-1 s-1, respectively. The amperometric sensor has the following values for the determination of DA: linear range of 5-120 μmol L-1 and limit of detection of 2.2 μmol L-1. The third part describes the development of a nanostructured platform based on CNT and electrochemically oxidized capsaicin (CAP) for the determination of dopamine (DA) and epinephrine (EP). Thus, by means of chronoamperometric studies and Cottrell's equations, it was possible to obtain the values in relation to DA: DDA of 6.97 x 10-4 cm2 s -1 and kcat of 3.12 x 105 M -1 s -1, and in relation to EP, the values obtained were 4.00 × 10 -5 cm 2 s -1 and 2.41 × 104 M-1 s-1 for DEP and kcat, respectively. The amperometric sensor presented the following values in relation to the separate determinations of DA and EP: for DA, linear range of 5-115 μmol L-1 and detection limit of 1.8 μmol L-1; for EP, a linear range of 50-1150 μmol L-1 and a detection limit of 7.2 μmol L-1. Considering the results obtained in this work, the developed sensors justify their use for determination and quantification of 3-nitro-L-tyrosine, dopamine and epinephrine.